2022
DOI: 10.31674/mjn.2022.v13i03.013
|View full text |Cite
|
Sign up to set email alerts
|

Planned Teaching Programme Through Booklet for Primi Gravidae Women Regarding Lacatation Problems

Abstract: Introduction: Lactation issues are a painful ailment that affects postpartum women and leads to failed breastfeeding. As a result, there is a strong need to improve women's awareness and self-care behaviors related to breast problems especially among primi gravidae. Aim: to evaluate the effect planned teaching programed through booklet for primi gravidae women regarding Lactation problems. A quasi-experimental design was utilized. Setting: The study was done at antenatal clinic of Suez Canal university Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…If a pregnant mother has a low perception of exclusive breastfeeding, then most likely their motivation to perform early initiation of breastfeeding will not be fully realized due to their lack of knowledge and reluctance to perform early initiation of breastfeeding. Another study shows that primi moms had poor knowledge and practice about breastfeeding and face a lot of trouble after childbirth with latching, according to the study's findings (Ibrahiem et al, 2022).…”
Section: Discussion Pregnant Mothers' Perception Of Exclusive Breastf...mentioning
confidence: 92%
“…If a pregnant mother has a low perception of exclusive breastfeeding, then most likely their motivation to perform early initiation of breastfeeding will not be fully realized due to their lack of knowledge and reluctance to perform early initiation of breastfeeding. Another study shows that primi moms had poor knowledge and practice about breastfeeding and face a lot of trouble after childbirth with latching, according to the study's findings (Ibrahiem et al, 2022).…”
Section: Discussion Pregnant Mothers' Perception Of Exclusive Breastf...mentioning
confidence: 92%
“…Another study done by Ibrahiem (2022) reported booklet distribution during the antenatal clinic will increase the knowledge among primi gravidae mothers. This study was focused on the lactation problem, but the nurses can implement this for PIH information, especially for primi gravidae mothers, and it may help to increase the mothers' knowledge (Ibrahiem et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A Malaysian study has indicated that women's own past experiences of abnormal pregnancy or labor led to increased knowledge regarding the dangerous signs in pregnancy (Teng et al, 2015). Another study done by Ibrahiem (2022) reported booklet distribution during the antenatal clinic will increase the knowledge among primi gravidae mothers. This study was focused on the lactation problem, but the nurses can implement this for PIH information, especially for primi gravidae mothers, and it may help to increase the mothers' knowledge (Ibrahiem et al, 2022).…”
Section: Discussionmentioning
confidence: 99%